A non-specialist worker delivered digital assessment of cognitive development (DEEP) in young children: A longitudinal validation study in rural India. - Supriya Bhavnani; Alok Ranjan; Debarati Mukherjee; Gauri Divan; Amit Prakash; Astha Yadav; Chaman Lal; Diksha Gajria; Hiba Irfan; Kamal Kant Sharma; Smita Todkar; Vikram Patel; et al. (PLOS Digital Health)
Cognitive development in early childhood is critical for life-long well-being. Existing cognitive development surveillance tools require lengthy parental interviews and observations of children. Developmental Assessment on an E-Platform (DEEP) is a digital tool designed to address this gap by providing a gamified, direct assessment of cognition in young children which can be delivered by front-line providers in community settings. This longitudinal study recruited children from the SPRING trial in rural Haryana, India. DEEP was administered at 39 (SD 1; N = 1359), 60 (SD 5; N = 1234) and 95 (SD 4; N = 600) months and scores were derived using item response theory. Criterion validity was examined by correlating DEEP-score with age, Bayley's Scales of Infant Development (BSID-III) cognitive domain score at age 3 and Raven's Coloured Progressive Matrices (CPM) at age 8; predictive validity was examined by correlating DEEP-scores at preschool-age with academic performance at age 8 and convergent validity through correlations with height-for-age z-scores (HAZ), socioeconomic status (SES) and early life adversities. DEEP-score correlated strongly with age (r = 0.83, 95% CI 0.82 0.84) and moderately with BSID-III (r = 0.50, 0.39 - 0.60) and CPM (r = 0.37; 0.30 - 0.44). DEEP-score at preschool-age predicted academic outcomes at school-age (0.32; 0.25 - 0.41) and correlated positively with HAZ and SES and negatively with early life adversities. DEEP provides a valid, scalable method for cognitive assessment. It's integration into developmental surveillance programs could aid in monitoring and early detection of cognitive delays, enabling timely interventions.